USE OF OFFICE 365 MEDIA FOR EDUCATION AND WEB BLOG AS ALTERNATIVES FOR NETWORK LEARNING - Yayan - Yayan; Wikanengsih - Wikanengsih (JLER (Journal of Language Education Research), 2021)
This study aims to describe the learning process with the Whatshap Application, Office 365 for Education, and Web Blog, as well as the difficulties experienced by teachers and students while learning. This research is an experimental method with a sample population of eighth grade students of SMP Negeri 3 Rongga amounting to 30 people. Data collection was carried out using obesity and test techniques. The instrument used was the microsoft form questionnaire sheet and the question sheet with multiple choice forms. Research validation was tested with external validity. Data analysis techniques were used to analyze learning success using SPSS. The results of this study are 1) Learning with Whatshap, Office 365 for Education, and Web Blog begins with the creation of Whatsapp Group student account registration in Office 356 For Education, Download and installation of Microsoft Team applications needed in the student apparatus, implementation of learning, and evaluation with microsoft form 2) Difficulties felt by students when online learning is the average student feels difficulty in using applications.